PENILAIAN FASILITAS GEDUNG TERMINAL BANDARA INTERNASIONAL SULTAN SYARIF KASIM II PEKANBARU - Monica Anggun Ayu Prawisty; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The tourism industry is industry that growing very rapidly in the world, the tourism industry is very closely related to its aviation industry. Due to the rapid development in tourism world, will affect the high use of air transportation as a means used for tourists to travel to tourist destination. Through air transportation will greatly facilitate tourists to be able to visit a tourist destination be it in the country or abroad and also will save more time when compared with land and sea transportation.The air transportation is closely related to the Airport. Airport is an airfield, including any buildings and equipment that are minimal to ensure the availability of facilities for air transport to the public. The purpose of this research is to know the airplane passenger’s valuation of terminal building facilities at Sultan Syarif Kasim II International Airport Pekanbaru.This research uses quantitative descriptive approach with quantitative and qualitative data types to analyze problem. The sample used is 100 respondents and the data obtained through questionnaires, observation and documentation. By using Likert scale as a measuring tool. The results of the research showed the airplane passenger’s valuation of terminal building facilities from various indicators are categorized good. The conclusion of this research is the existing facility in the airport terminal building with good category and the writer's suggestion for airport management is to maintain the condition of the existing facility so that airplane passenger’s valuation on existing facility always good and will be better in the future.Keywords : Valuation, Facilities, Airport Terminal Building